Harvest Maturity for Mango (Mangifera Indica L.) Fruit Based on Accumulated Day-Degrees (C), Rainfall Amount (mm), and Physical Fruit Development Properties - Abu, Moomin; Olympio, Nana Sakyiwa; Darko , Joseph Ofei (Research Highlights in Agricultural Sciences Vol. 1, 2022)
Haden, Kent, Palmer, and Keitt mango varieties were studied to establish the relationship of harvest time to seasonal accumulated day-degrees or heat units (C), daily rainfall amount (mm), and physical fruit development attributes with the objective to fix maturity standards for export and local markets. Randomized Complete Block Design was used with four replications. Physical fruit development characteristics that are designated as standard harvest maturity values were found in each of the Haden, Kent, Palmer, and Keitt types : weight (640 g, 836 g, 837 g, and 1104 g, respectively), length (16.31 cm, 16.19 cm, 21.22 cm, and 19 cm, respectively), width (30.97 cm, 33.47 cm, 30.86 cm, and 35.91 cm, respectively), volume (598 cm3, 807 cm3, 772 cm3, and 959 cm3, respectively), density (1.147 g/cm3, 1.076 g/cm3, 1.084 g/cm3, and 1.189 g/cm3, respectively), and indentation (0.25 cm, 0.49 cm, and 0.50 cm, respectively). Palmer fruits' stylar-scar end groove intensity was investigated and utilised as a ripeness indicator. For the Haden, Kent, Palmer, and Keitt varieties, index values of 0.075 mls, 0.150 mls, 0.425 mls, and 0.116 mls, respectively, were recorded as latex exuded at harvest because these values agreed with the other physical harvest maturity index values as well as with those of rain fall and temperature. This makes temperature, rainfall, and physical attributes crucial non-destructive variables for determining mango fruit maturity index values.